Analysis of the Influence of Capital Market Level, Mindset, and Minimum Capital on Investment Interest of Bangka Belitung University Students with Investment Risk as Moderating Variable - Berthalia, Fifi; Mareta, Nela; Amanda, Lola; Julia (Future Science / FSH-PH Publications, 2023)
This study aims to determine whether there is an influence on the level of capital market knowledge, mindset, and minimal capital with investment risk as a moderating variable. This research was conducted at the Faculty of Economics, Bangka Belitung University. The method in the research used is the quantitative method from the primary data. Data collection using the questionnaire method is in the form of respondents' answer results expressed in the form of numbers from questionnaires measured using the Likert scale. The results in this study are that the level of knowledge of the capital market, mindset and minimal capital have a significant positive effect on students' investment interests, while the relationship between investment risks is able to moderate the variable level of knowledge and minimal capital to the influence of student investment interests. The relationship of investment risk is not able to moderate the mindset variables to the influence of students' investment interests. In this study, it was shown that there were 55,7% influence and the remaining 44,3% influenced by other factors.